Comparison of situs ambiguous patterns between heterotaxy syndromes with polysplenia and asplenia. Issue 11 (November 2015) - Yoneyama, Hiroko; Kondo, Chisato; Yamasaki, Aki; Nakanishi, Toshio; Sakai, Shuji
Highlights: This article describes ambiguous patterns of polysplenia and asplenia syndrome as shown by CT. Between these syndromes, significant differences in venous malformations and tracheobronchial anomaly were observed. To our knowledge, abnormal confluence of renal vein complicated with asplenia has not been reported previously. Since these syndromes are rarely encountered in clinical settings, this study may help general radiologists and facilitate diagnostic processes by sharing characteristic features of the cardiac, thoracic and abdominal and anomalies associated with polysplenia and asplenia syndrome. We feel that findings from this study will be of special interest to the readers of European Journal of Radiology. Abstract: Objectives: To compare the differences of visceral anomalies shown by computed tomography (CT) in patients with polysplenia syndrome (PS) or asplenia syndrome (AS). Methods: This retrospective study was approved by the institutional review board, and informed consent was waived. Thirty-one patients with PS and 29 patients with AS underwent chest-abdominal CT. The evaluated CT findings were as follows: the orientation of stomach, liver and gallbladder; short pancreas; azygous/hemiazygous continuation; ipsilateral position of the inferior vena cava and aorta; preduodenal portal vein; abnormal confluence of renal vein (defined as renal vein drains to the inferior vena cava or azygous/hemiazygous vein at the upper level of celiac trunk origin); gastrointestinal malrotation; and tracheobronchial tree. Results: Azygous/hemiazygous continuation was seen in 74% (20 of 27)/0% (0 of 28) of PS/AS ( P  < 0.0001), bilateral hyparterial bronchi in 75% (24 of 32)/5% (1 of 22), bilateral eparterial bronchi in 9% (3 of 32)/95% (21 of 22), ipsilateral position of the inferior vena cava and aorta in 59% (16 of 27)/89% (25 of 28), and abnormal confluence of renal vein in 7% (2 of 27)/57% (16 of 28), respectively. No significant differences were found in the other anomalies. Conclusion: Significant differences in anomalous systemic venous connections and tracheobronchial anomaly were observed between PS and AS. Abnormal confluence of renal vein is relatively rare anomalous venous connections, but frequently observed in AS.